Towards the Development of a Mobile Agriculture System for Poms Poultry Farm (PPF), Oyarifa-Accra, Ghana - Nana Yaw Asabere; Amevi Acakpovi; Vida Kumiwaa Owusu; Jerry Abudu Attah; Eugene Kyeremateng Opoku (Journal of Digital Food, Energy & Water Systems)
This paper seeks to propose the implementation of a mobile agriculture (m-agriculture) system for Poms Poultry Farm (PPF) to solve problems such as low patronage of farm products and customer relationship management among farmers and customers. To corroborate the successful implementation of an m-agriculture system at PPF, we employed a questionnaire research instrument concerning the Technology Acceptance Model (TAM) model as a theoretical framework. Closed-ended questionnaires were administered to a sample size of 130 PPF customers. Based on the responses received, we established optimistic responses towards technological acceptance which paved the way for us to propose and develop a suitable m-agriculture application for PPF. It is envisaged that successful implementation of our proposed system will practically increase productivity and help PPF reach out to their target customers.